Hubungan jarak kelahiran dan jumlah anak dengan status gizi anak taman kanak-kanak - Bambang Edi Prasetyo; Endy Paryanto Prawirohartono; Rahyaningsih Rahyaningsih (Jurnal Gizi Klinik Indonesia, 2008)
Background: Parents’ attention is needed in the growth and development of children. Nowadays, there are families consisted more than 3 children with short birth interval. It causes parents’ love, attention, and daily needs (especially food) become less.Objectives: The study was conducted to know the relationship between birth interval and number of children in a family and nutritional status of kindergarten children.Methods: The study was observational with cross sectional design. The samples were kindergarten children in Wates District who met the inclusion and exclusion criteria. The inclusion criteria were children allowed by their parents to become samples and had at least one sister/brother; whereas the exclusion criteria were children that were sick. The sample size was 193, determined using single sample hypothesis formula. Chi square was used to analyze data.Results: The study showed that birth interval influenced mothering way indirectly (p=0.003), but mothering way did not influence food intake statistically (p=0.73). Food intake influenced nutrition status directly (p=0.001). Number of children did not influence mothering way statistically (p=0.49).Conclusions: Birth interval influences the nutrition status indirectly. There was no relationship between number of children and nutrition status of kindergarten children.